Modeling the thermomechanical behaviors of short fiber reinforced shape memory polymer composites. (15th January 2020) - Zeng, Hao; Leng, Jinsong; Gu, Jianping; Sun, Huiyu
Highlights: The paper provides a thermal viscoelastic finite deformation constitutive model for thermally activated short fiber reinforced shape memory polymers. The key feature of the model is the modified temperature-dependent laminate analogy theory for the prediction of the thermal-dependent effective elastic properties of the composites. Simulation results of the elastic, plastic, yielding, post-yielding and shape memory behaviors of the composites are obtained and compared with the experimental data. Abstract: Short fiber reinforced shape memory polymer composites (SF-SMPCs) possess better mechanical properties compared to pure shape memory polymers, and in the meantime, keep the high deformability and the good shape memory properties. In the paper, a thermoviscoelastic finite deformation constitutive model is developed for thermally activated SF-SMPCs. The key of the model is the modified temperature-dependent laminate analogy theory for the prediction of the thermal-dependent effective elastic properties of the composites of different fiber volume fractions. The constitutive theory is based on a generalized three-element model consisting of a hyperelastic branch and a viscoelastic branch, in which the volume fraction dependent yielding properties are described by a modified Eying model. The developed constitutive model is then implemented into Mathematica to simulate the thermomechanical behaviors of the materials under different loadings, and the simulation results show great agreements with the experimental data. Finally, the shape memory effects of the SF-SMPCs are studied by a typical free-recovery thermomechanical cycle. The shape fixity and shape recovery speed are slightly influenced by the reinforcements, and the shape recovery ratios are almost 100% for all SF-SMPCs. The paper offers an efficient method to theoretically describe and predict the thermomechanical behaviors of SF-SMPCs. Graphical abstract: Image, graphical abstract